2015
DOI: 10.1021/acscatal.5b01102
|View full text |Cite
|
Sign up to set email alerts
|

Selective Alkylation of Benzene with Propane over Bifunctional Pt-Heteropoly Acid Catalyst

Abstract: The alkylation of benzene with propane to yield isopropylbenzene proceeds with high selectivity over bifunctional metal-acid catalysts comprising Pt and Keggin heteropoly acid in a fixed-bed reactor at 250-350 o C and 1 bar pressure. Most efficiently the reaction occurs over Pt/H 4 SiW 12 O 40 /SiO 2 catalyst at 300 o C, giving isopropylbenzene with 90-93% selectivity at 6-8% benzene conversion, significantly exceeding the efficiency of previously reported Pt/HZSM-5 catalyst. The alkylation proceeds through bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 37 publications
5
25
0
Order By: Relevance
“…Also, we looked at the effect of gold additives on catalyst performance by testing the corresponding AuPd-HSiW and AuPd-HZSM-5 bimetallic catalysts. It is demonstrated that in benzene alkylation with propane, the Pd-HSiW and Pd-HZSM-5 catalysts perform similarly to their Pt counterparts, Pt-HSiW and Pt-HZSM-5, as reported previously [18]. The addition of gold to Pd-HSiW is shown to enhance the activity of this catalyst, although the Au-HSiW without Pd is inert.…”
Section: Introductionsupporting
confidence: 74%
See 4 more Smart Citations
“…Also, we looked at the effect of gold additives on catalyst performance by testing the corresponding AuPd-HSiW and AuPd-HZSM-5 bimetallic catalysts. It is demonstrated that in benzene alkylation with propane, the Pd-HSiW and Pd-HZSM-5 catalysts perform similarly to their Pt counterparts, Pt-HSiW and Pt-HZSM-5, as reported previously [18]. The addition of gold to Pd-HSiW is shown to enhance the activity of this catalyst, although the Au-HSiW without Pd is inert.…”
Section: Introductionsupporting
confidence: 74%
“…It is essential to compare the bifunctional Pd catalysts under study with previously reported Pt catalysts [18] under the same reaction conditions. Therefore, the Pd catalysts were tested in benzene alkylation with propane in the same system at 300 • C, contact time W/F = 80 g h mol −1 and [C 6 H 6 ]/[C 3 H 8 ] = 1:9 mol/mol without dilution of the gas feed with an inert gas, as described previously [18].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations